Strategic leading of digital transformation in Brunei to propel digital economy - Abidin, Abdul Qawie; Ramachandiran, Chandra Reka; Ghosh, Shounak (Journal of Applied Technology and Innovation, 2021)
Digital Economy is the integration of digital technology into all aspects of social and economic activities, essentially changing the way citizens, consumers, and businesses communicate and perform work. The rapid advancement of technological innovation will continuously cause digital disruption by which, with proper digital competences and strategic leadership, can be leveraged as an essential element to create opportunities and problem solving, otherwise, it would further widen the digital divide. This study review will be based on the previous academic study in the latest five years; the concept of the digital economy; drivers and enablers of the digital economy, importance of digital economy policies; and role of leadership in digital transformation. The main aim of this paper is to provide some general review in regard to strategically lead the digital transformation of the digital economy in Brunei by propelling the policies.